Pregnancy outcomes and vaccine effectiveness during the period of omicron as the variant of concern, INTERCOVID-2022: a multinational, observational study - Villar, J; Conti, CPS; Gunier, RB; Ariff, S; Craik, R; Cavoretto, PI; Rauch, S; Gandino, S; Nieto, R; Winsey, FA; Menis, C; Rodriguez, GB; et al. (Lippincott, Williams & Wilkins, 2023)
In 2021, COVID-19 during pregnancy was reported to be associated with an increased risk of maternal and neonatal outcomes. The SARS-CoV-2 virus has undergone genetic mutations since then and the subsequent impact of the omicron variant on maternal and neonatal health wasunknown. This study aimed to analyze the effects on maternal and perinatal outcomes of omicron during pregnancy as well as vaccine efficacy.